Інгібітори циклооксигенази-2 в терапії кішок із пухлинами молочної залози (короткий огляд) - Білий, Дмитро Дмитрович; Beliy, Dmitry Dmitrievich; Beliy, Dmitry; Beliy, D. D.; Bely, Dmitry Dmitrievich; Bely, Dmitry; Bely, D. D.; Bilyi, D. D.; Bilyi, D.; Belyi, D. D.; Bilyi, Dmytro; Bily, Dmytro; et al. (Одеський ДАУ, 2023)
Прогресивне збільшення частки кішок із новоутвореннями молочної залози на тлі недостатньої ефективності лікування обумовлює необхідність розробки і впровадження альтернативних схем лікування. Одним із перспективних напрямків є вплив на прозапальну ланку, зокрема шляхом гальмування синтезу циклооксигенази-2. За неоплазій молочної залози у кішок доведена протипухлинна активність мелоксикаму, робенакоксибу, аспірину, піроксикаму. У 30 % пацієнтів побічні ефекти при їх використанні короткочасні і не потребують корекції, тільки у 10 % випадків зумовлюють необхідність переривання терапії. Наразі перспективним напрямком є дослідження можливості довготривалого застосування в онкохворих кішок інгібіторів циклооксигенази-2. The progressive increase in the proportion of cats with mammary gland neoplasms against the background of insufficient treatment efficiency necessitates the development and implementation of alternative treatment schemes. One of the promising directions is the influence on the pro-inflammatory link, in particular by inhibiting the synthesis of cyclooxygenase-2. Unlike humans, the issue of the feasibility of their use in cats remains debatable, which is associated with various data on the expression level of cyclooxygenase-2 in cancer patients and insufficient study of its role in the mechanisms of carcinogenesis. The evidence base for the effectiveness of NSAIDs for mammary gland cancer in cats is currently based on the results of a few clinical trials. In addition to anti-inflammatory effects, cyclooxygenase-2 inhibitors initiate apoptosis, inhibit the cell cycle and migration of cancer cells. Their maximum concentration is recorded in the affected areas, which ensures a high level of biosafety for patients. The antitumor activity of meloxicam, robenacoxib, aspirin, and piroxicam has been proven for mammary gland neoplasia in cats. Side effects of the use of non-steroidal anti-inflammatory drugs can be manifested by disorders of the cardiovascular and excretory systems, the gastrointestinal tract, hematopoiesis. In 30% of patients, side effects during their use are short-term and do not require correction, only in 10% of cases they cause the need to interrupt therapy, which is caused by selectivity to cyclooxygenase-2. The results of pilot studies on cats with mammary gland neoplasia demonstrate the feasibility of including cyclooxygenase-2 inhibitors in treatment protocols in order to reduce the toxic load on the body from chemotherapeutic agents. The high level of selectivity for cyclooxygenase-2 and the moderate risk of unwanted effects allow us to consider the possibility of long-term use of nonsteroidal anti-inflammatory drugs in cats with cancer as a promising direction for further research.
Cyclooxygenase-2 inhibitors in the treatment of cats with mammary tumors (brief review)
Білий Дмитро Дмитрович https://orcid.org/0000-0003-3896-0384
Keywords: нестероїдні протизапальні засоби; nonsteroidal anti-inflammatory drugs; кішки; cats; новоутворення молочної залози; neoplasms of the mammary gland; циклооксигеназа-2; cyclooxygenase-2